A Science on the Scales : The Rise of Canadian Atlantic Fisheries Biology, 1898-1939 - Hubbard, Jennifer Mary, 1960- (Book collections on Project MUSE., 2006)
An original and timely work, A Science on the Scales shines a light on a heretofore-neglected aspect of Canada's science history.